UTILIZATION OF PICTURE MEDIA IN LEARNING SBDP ILLUSTRATION MATERIAL FOR GRADE V STUDENTS OF STATE ELEMENTARY SCHOOL 5, BANDA ACEH CITY - Miko, Jufri Temas; Fitri, Aida; Safiah, Intan (Universitas Syiah Kuala, 2025)
The purpose of this study was to find out the Utilization of Picture Media and student learning outcomes in SBdP Learning Illustrated Picture Materials for Grade V Students of SD Negeri 5 Banda Aceh City. This research uses a qualitative approach with a descriptive type. The research was conducted at SD Negeri 5 Banda Aceh. The research subjects were Class V-A students for the 2022/2023 academic year, which consisted of 23 students consisting of 10 male students and 13 female students. The research instruments used were observation sheets, tests and a list of questions and other observations to obtain research data. Data collection techniques were carried out by observation and tests. The data analysis technique used by the study uses the Miles and Huberman model, namely percentages, data reduction, data presentation, and drawing conclusions. Picture Illustration of Grade V Students at SD Negeri 5 Banda Aceh City is already good. Painting picture media can be a very effective tool in improving learning outcomes because it can improve visual memory helping students to remember information more easily because it can show pictures or illustrations that can give a stronger impression on students' brains. It is hoped that future researchers will examine more deeply with a comparison of two schools using the use of media images in the learning process stract contains a brief description of the research objectives, methods used, instruments, data analysis techniques, and research results. The emphasis of writing abstracts is mainly on research results. Abstracts are written in Indonesian and English. Abstract typing is done single-spaced with margins that are narrower than the right and left margins of the main text. Keywords need to be included to describe the realm of the problem under study and the main terms that underlie the implementation of the research. Key words can be single words or a combination of words. The number of key words 3-5 words. These key words are necessary for computerization. Searching for research titles and abstracts is made easier with these key words.